2016
DOI: 10.4236/ce.2016.711158
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Constraints of the Use of Information and Communication Technology (ICT) in Teaching Mathematics

Abstract: The development of information and communication technology (ICT) has affected educators' teaching methods through its application in learning and teaching mathematics. The objective of this systematic analysis is to explore the benefits and constraints of ICT that have been faced by educators during learning and teaching processes for mathematics. Based on selected literature, it was found that the advantages of applying ICT in teaching mathematics are: It attracts students' interest in learning mathematics; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…This perception also works in reverse, in that if a user feels the benefits of using e-Daftar while performing their tasks, they will automatically feel that it is easy to use. This statement is supported by Muntianah et al (2012) and Zakaria & Khalid (2016), who state thatthe easier a user feels it is to use a technology, the greater the benefits received by the user.…”
Section: Discussionmentioning
confidence: 85%
“…This perception also works in reverse, in that if a user feels the benefits of using e-Daftar while performing their tasks, they will automatically feel that it is easy to use. This statement is supported by Muntianah et al (2012) and Zakaria & Khalid (2016), who state thatthe easier a user feels it is to use a technology, the greater the benefits received by the user.…”
Section: Discussionmentioning
confidence: 85%
“…There are several qualitative pieces of evidence in the current research body concerning the impacts and benefits of infusing ICT in mathematical pedagogies. These include improvement in learner's performance [27], increase in enthusiasm and curiosity in mathematics [27,28], creation of active and authentic learning environment [29,30], and expansion of creativity and critical thinking skills [27], thus leading to constructive learning and higher-order thinking [31], while also improving learner's learning attitudes and experiences [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previously, [51] also found that mathematics self-efficacy and mathematics anxiety significantly affect mathematics performance in Malaysia and Singapore. Consequently, as students' attitudes and interests can be fostered with learning and teaching pedagogies [27], mathematics teachers are striving to rekindle interest and energy in their teaching environment, encourage towards mathematic learning, and offer the world-class learning experience to their students.…”
Section: Issues and Challenges In Mathematics Education In The Regionmentioning
confidence: 99%
“…It is an undeniable fact that the way people learn, retrieve information, and construct knowledge has changed with the existence of the Internet and digital media [1], [2]. Although the Internet is considered the most valuable innovation ever created, it also has a dark side that may result in adverse effects on its users, including adults and children [3]- [5].…”
Section: Introductionmentioning
confidence: 99%